Cahaya Pengusir Hama : Penerapan LumiTrap UV Surya pada Cabai Kebun Sumber Berkah - Fulkha Tajri M; Riyan Benny Sukmara; Juwita Permata Sari; Leni Pratiwi; Albarthina Novirna; Ratna Dia Paramita; Alwan Akmal Larik; Ariel Athaillah Kheristiawan; Zaky Ramadhani Setyo Albukhari; Kurnia Sari (Lok Seva: Journal of Contemporary Community Service, 2026)
Chili productivity on urban farming land is often hindered by nocturnal insect pest attacks, as experienced at Kebun Sumber Berkah, RT 37, Batu Ampar, Balikpapan City. Pest control has relied on chemical pesticide spraying two to three times weekly, incurring high costs and health risks for garden workers. This community service activity aimed to implement LumiTrap UV, an ultraviolet-light pest trap powered by an independent solar panel system, as an environmentally friendly pest-control alternative. The implementation method comprised survey and preparation, design and installation of six LumiTrap UV units, socialization for partners, and sustainability monitoring, involving nine students under the supervision of two lecturers. Results show that all six units were successfully installed and operate automatically at night using independent solar energy, partners gained skills in operating and maintaining the device, and three residents were appointed as sustainability champions. Preliminary observations indicate a declining trend in pest presence around the plants and a reduction of about 50–67% in the frequency of chemical pesticide spraying by partners (from two to three times weekly to about once a week).